2023
DOI: 10.3389/fevo.2023.1155783
|View full text |Cite
|
Sign up to set email alerts
|

Assessing uncertainty in genomic offset forecasts from landscape genomic models (and implications for restoration and assisted migration)

Abstract: IntroductionEcological genomic models are increasingly used to guide climate-conscious restoration and conservation practices in the light of accelerating environmental change. Genomic offsets that quantify the disruption of existing genotype–environment associations under environmental change are a promising model-based tool to inform such measures. With recent advances, potential applications of genomic offset predictions include but are not restricted to: (1) assessing in situ climate risks, (2) mapping fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…Because of the assumption that locally adapted populations will be necessary for satisfactory model performance, initial implementations of genomic offset models focussed on putatively adaptive markers where this signal may be strongest (Keller & Fitzpatrick, 2015; Rellstab et al, 2016). More recently, investigators have varied the set of markers used to train models but have found little influence on performance (Fitzpatrick et al, 2021; Lachmuth, Capblancq, Keller, et al, 2023; Láruson et al, 2022; Lind et al, 2024). Our results are similar to previous investigations, finding that the adaptive marker sets provide minimal advantage over all or neutral marker sets, but not universally or by great margins.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of the assumption that locally adapted populations will be necessary for satisfactory model performance, initial implementations of genomic offset models focussed on putatively adaptive markers where this signal may be strongest (Keller & Fitzpatrick, 2015; Rellstab et al, 2016). More recently, investigators have varied the set of markers used to train models but have found little influence on performance (Fitzpatrick et al, 2021; Lachmuth, Capblancq, Keller, et al, 2023; Láruson et al, 2022; Lind et al, 2024). Our results are similar to previous investigations, finding that the adaptive marker sets provide minimal advantage over all or neutral marker sets, but not universally or by great margins.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis put forth as to why adaptive marker sets perform similarly to all markers is that genome-wide data captures sufficient signatures of IBE (Lachmuth, Capblancq, Keller, et al, 2023; Lind et al, 2024). Our analysis found weak positive relationships between performance and levels of IBE within marker sets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations